A Design Technique for Adapting Number and Boundaries of Reconfigurable Modules at Runtime. (15th July 2009) - Pionteck, Thilo; Koch, Roman; Albrecht, Carsten; Maehle, Erik
Abstract : Runtime reconfigurable system-on-chip designs for FPGAs pose manifold demands on the underlying system architecture and design tool capabilities. The system architecture has to support varying communication needs of a changing number of processing units mapped onto diverse locations. Design tools should support an arbitrary placement of processing modules and the adjustment of boundaries of reconfigurable regions to the size of the actually instantiated processing modules. While few works address the design of flexible system architectures, the adjustment of boundaries of reconfigurable regions to the size of the actually instantiated processing modules is hardly ever considered due to design tool limitations. In this paper, a technique for circumventing this restriction is presented. It allows for a rededication of the reconfigurable area to a different number of individually sized reconfigurable regions. This technique is embedded in the design flow of a runtime reconfigurable system architecture for Xilinx Virtex-4 FPGAs. The system architecture will also be presented to provide a realistic application example.